Feasibility of Butterfly Pea Plant Plant Booklet (Clitoria ternatea L.) as Learning Media - Panjaitan, Ruqiah Ganda Putri; Tenriawaru, Andi Besse; Hayati, Nurul; Minderman, Nasreen Nischka; Murni, Odela Priscilia (Jurnal Penelitian Pendidikan IPA, 2023)
Learning media is a tool that teachers can use to improve the quality of learning. Making learning media can be compiled based on the results of previous research literature studies on an object. The purpose of this study was to determine the feasibility of learning media for Clitoria ternatea L. booklets. The stages in this research are carried out by collecting information through literature studies related to falconry plants, booklet preparation, booklet validation, and booklet revision based on suggestions from both validators. Booklet assessment covers aspects of format, content, and language. The results of validation by validators are then analyzed using Gregory. The results of the data that have been analyzed show that aspects of format, content, and language get a value of 1.00 and these three aspects have an average of 1.00 with a very high validity category. Thus, it can be concluded that this eagle plant booklet is suitable to be used as a learning medium.